Selected Topics on Optical Fiber Technologies and Applications - Xu, Fei; Mou, Chengbo (IntechOpen, 2018)
This book is a collection of contributions by selected active researchers in the optical fiber fields highlighting the design, fabrication, and application of optical fibers and fiber systems and covering various topics such as microstructured optical fibers, polymer fibers, nonlinear effects, optical tweezers, and gyroscopic systems. The goal of the book is to provide an updated overview of the current research trends in the optical fiber fields, serving as a general reference for the recent development in optical fiber technologies, though inevitably many topics are not covered.